2019
DOI: 10.1038/s41390-019-0696-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel delivery system for supraglottic atomization allows increased lung deposition rates of pulmonary surfactant in newborn piglets

Abstract: BACKGROUND: Earlier attempts to deliver effective lung doses of surfactant by aerosolization were unsuccessful, mostly because of technical shortcomings. We aimed at quantifying the lung deposition of poractant alfa with a new supraglottic delivery system for surfactant atomization in an experimental neonatal model. METHODS: The method involved six sedated 1-day-old piglets lying in the lateral decubitus, spontaneously breathing on nasalmask continuous positive airway pressure (nCPAP). A pharyngeal cannula hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Taking these observations as a starting point, different strategies for intracorporeal, yet supraglottic (i.e., non-invasive), atomization have been developed [15,[34][35][36]. In this regard, Linner et al have recently reported a 40% lung surfactant deposition after delivering a 200 mg/kg dose of technetium-labeled Poractant alfa to healthy, neonatal piglets managed with CPAP [37]. The key to this remarkable result was most likely the synchronization between the aerosol generator and the inspiratory effort of the animal.…”
Section: Discussionmentioning
confidence: 99%
“…Taking these observations as a starting point, different strategies for intracorporeal, yet supraglottic (i.e., non-invasive), atomization have been developed [15,[34][35][36]. In this regard, Linner et al have recently reported a 40% lung surfactant deposition after delivering a 200 mg/kg dose of technetium-labeled Poractant alfa to healthy, neonatal piglets managed with CPAP [37]. The key to this remarkable result was most likely the synchronization between the aerosol generator and the inspiratory effort of the animal.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are no previous reports of such a significant in vivo lung deposition of nebulized surfactant in a neonatal model with an entirely noninvasive interface. Apart from our earlier study in the lateral decubitus showing 14% deposition with the same eFlow-Neos investigational nebulizer [10], and two quasi-noninvasive atomization studies with a rigid supraglottic cannula with deposition of 32% of the nominal dose in preterm lambs [19] and 40% in neonatal piglets [20], the best result ever obtained by a noninvasive technique was a lung deposition of less than 1% of the administered surfactant in preterm lambs [7], which took 3 h. Comparably, in our study, although poractant alfa has the highest phospholipid content of all available exogenous surfactants, nebulization of 2.5 mL kg –1 of the undiluted drug took between 16 and 19 min, which gives a mean output range of 0.22–0.27 mL min –1 , close to the average output for aqueous solutions with standard nebulizers [18].…”
Section: Discussionmentioning
confidence: 99%
“…Inhalation or atomizing catheters are proposed as a method to deliver surfactant during NIV [80][81][82]. Unlike most aerosol devices, which create droplets outside the patient, atomizing catheters are designed to maximize the dose delivered to the lung by generating intra-corporeal, yet extra-thoracic, aerosols.…”
Section: Table 1 Representative Respiratory Indices Across the Lifespanmentioning
confidence: 99%
“…Unfortunately, no information regarding aerosol particle size distribution (APSD) or lung deposition was provided, which may raise questions on the claim that the clinical benefit observed in a subset of the population studied can be attributable to aerosolized surfactant without any doubt. A slightly different strategy of aerosolization was described in a series of late-stage preclinical investigations [81,82]: an alternative atomizing catheter was kept in place by a custom-made interface placed in the retro-pharynx close to the vocal cords, fostering intra-tracheal deposition. This technology is effective in delivering surfactant (Poractant alfa, Curosurf ® ) to preterm lambs with nRDS managed with nCPAP [81].…”
Section: Table 1 Representative Respiratory Indices Across the Lifespanmentioning
confidence: 99%
See 1 more Smart Citation